Image quality improvement of magneto-acousto-electrical tomography with Barker coded excitation. (August 2022) - Deng, Dingqian; Sun, Tong; Yu, Linguo; Chen, Yi; Chen, Xin; Chen, Mian; Chen, Siping; Lin, Haoming
Abstract: Magneto-acousto-electrical tomography (MAET) combines the advantages of the high resolution of ultrasound imaging and the high contrast of electrical impedance tomography for imaging the conductivity of tissues. The traditional MAET uses a short pulse as the excitation waveform, and the amplitude of the MAE signal for a single acquisition is very weak. Thus, the multiple-acquisition mode for averaging was adopted to reduce the system noise while significantly increasing the data acquisition time. In this study, a coded-based MAET method was proposed to improve the image quality of MAET. We theoretically derived the principle of the coded-based MAET and analyzed the performance of different pulse compression techniques. The 13-bit Barker code was selected, and phantoms of different shapes and conductivity were used to verify the proposed method experimentally. Finally, in vitro experiment was conducted to investigate the performance of the proposed method in tissue level application. The experimental results show that the proposed method can significantly improve image quality and speed up the imaging time.